Emotional intelligence, parental attachment, and peer attachment as predictors of delinquent behaviour among secondary school students in Selangor, Malaysia - Lee, Phaik Gaik (2015)
This study aims to investigate whether emotional intelligence, parental attachment, and peer attachment predict the level of delinquent behaviour amongst secondary school students. The study also intends to ascertain the relationships between emotional intelligence, parental attachment, peer attachment and the delinquent behaviour amongst secondary school students, as well as to determine the extent to which emotional intelligence, parental attachment and peer attachment predict the level of delinquent behaviour amongst students. Data were gathered from a sample of 400 secondary school students aged 15- 18 in Selangor. Four instruments, namely, surveys on the ―Behaviour of Students‖, ―Malaysian Emotional Quotient Inventory (R)-Adolescence (MEQI)‖, ―Inventory of Parent attachment‖ and ―Inventory of Peer attachment‖ were utilised to collect the research data, which were analysed using descriptive and inferential statistics. This study utilised a correlation design to address the research objectives. The findings from this study show that among the six categories of delinquency, it was found that ‗disruption in school‘ was the highest (M=2.50, SD= .58) compared to the other categories. ‗Crime‘ (M=2.03, SD= .39) ranked second follow by ‗vandalism‘ (M=1.82, SD=.58) ranked third. The lowest category of delinquency was ‗drug‘ (M=1.16, SD=.60). This study also presented a complete profile of emotional intelligence whereby among the seven domains, self-awareness (M=42.59, SD= 11.66) was the lowest and spirituality (M= 74.50, SD= 10.56) was the highest. Mother attachment (M=3.50, SD=1.00) and peer communication (M=3.54, SD=.62) show the highest level in attachment among the students. The results also revealed a significant and negative relationship between emotional intelligence (r = - .465, p< .001), mother attachment (r = -.288, p< .001) and father attachment (r = -.146, p< .001). These findings imply that if emotional intelligence, mother attachment and father attachment of the adolescents increase, delinquency of the adolescents would decrease. In contrast, a significant and positive relationship was found between peer attachment (r=.225, p<.001) and delinquent behaviour. These findings imply that if adolescents had high attachment to the peers, the delinquency would also be high. Multiple linear regression analysis showed the combination of five predictors: emotional intelligence, mother attachment, father attachment, peer same gender, and peer different gender which accounts for 38.0% of the variation in delinquent behaviour R2 = .377. Emotional intelligence is the strongest predictor of delinquent behaviour. Hierarchical multiple regressions showed that gender moderated the relationship between peer same gender and peer different gender and delinquent behaviour of the students. It shows that male students were prone to delinquency. Similarly, family income moderated the relationship between mother attachment, father attachment, peer same gender and peer different gender and delinquent behaviour and delinquent behaviour. This study contributes to the knowledge of the importance of emotional intelligence in preventing delinquent behaviour. Promoting emotional intelligence in classroom plays is essential to help the students to regulate their emotions. Parents play an important role in the development of the adolescents. Parents who are supportive, convey emotional closeness with their children, would have a positive effect on thier children‘s behaviour. Finally, the results of this study provide a clear direction for the prevention of delinquent behaviour. Addressing the predictors, such as parental attachment and emotional intelligence would probably prove to be effective in reducing delinquent behaviour.